1974
DOI: 10.1159/000180375
|View full text |Cite
|
Sign up to set email alerts
|

Familial Renal Tract Abnormalities and Cortical Scarring

Abstract: A family group of first and second degree relatives is presented. Members of the group have vesico-ureteric reflux and/or duplex collecting systems. Renal scars of chronic pyelonephritis are seen. It is considered that because histological features are not always specific and because the relationship of renal scars to infection uncertain, chronic pyelonephritis is a diagnosis made on radiological evidence. It is suggested that the renal scars of this condition may result from vesico-ureteric reflux in infancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This technique also facilitates preschool screening and the earlier recognition of bacteriuria by health visitor and family doctor in a young sick child. The familial incidence of reflux and chronic pyelonephritis, which has been increasingly noted (Frye, Patel, and Parsons, 1974), may also provide a rewarding line of search for infants and children at risk.…”
Section: Screeningmentioning
confidence: 99%
“…This technique also facilitates preschool screening and the earlier recognition of bacteriuria by health visitor and family doctor in a young sick child. The familial incidence of reflux and chronic pyelonephritis, which has been increasingly noted (Frye, Patel, and Parsons, 1974), may also provide a rewarding line of search for infants and children at risk.…”
Section: Screeningmentioning
confidence: 99%
“…We are thinking of a hereditary factor involved in this case. Frey et al (1974) reported a family with several kidney deformities in three generations. Finn and Carruthers (1974) reported 2 families, who had 6 hydronephrctic members.…”
Section: Discussionmentioning
confidence: 99%
“…Vesicoureteral reflux has been found in up to five members of a family6 and spanning one to four generations.7 In one family reflux or other renal tract anomalies were found in eight firstor second-degree relatives. 8 Though this familial aggregation suggests a hereditary basis for at least some types of primary vesicoureteral reflux, there is no uniform pattern of inheritance. In one group of families it seems that the patients are almost exclusively male.7 9 Those described in detail have had severe reflux and extensive renal damage of the obstructive atrophy type; there has been little evidence of urinary tract infection.…”
Section: Vesicoureteral Reflux and Its Familial Distributionmentioning
confidence: 99%